(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-56-64 Abstract. Audiovisual content has significantly grown in popularity in the recent years. There have been numerous studies devoted to the peculiarities of audiovisual translation of materials, yet the majority of the research focuses solely on theoretical aspects. The article addresses the issue of comprehension and perception of audiovisual materials, as this issue is one of the most perspective and understudied questions of modern linguistics. The authors provide a brief analysis of the theoretical basis of the issue under discussion, referring to the research results of foreign and Russian scholars. The authors also describe the empiric-experimental analysis of German-language media perception by the Russian-speaking audience; summarize the results and outline the conclusions. The article covers the empiric-experimental psycholinguistic research based on the scaling method. The study contains the findings on the influence of the specifics of translation of chosen fragments of the series "Dark" on the audience’s perception and comprehension of the audiovisual materials translated into Russian, in comparison with the perception of the same fragments by the audience viewing the original content in German. The authors also formulate the perspectives for further study of the issue in question. The study indicated significant deviations in the translation of the content of some episodes, reflected in the perception disparity between the materials seen in the original and the translated versions. The results suggest that the translated material becomes less expressive; some of the scenes are misrepresented in terms of meaning. The potential for further research is to increase the scope of the material studied and to use additional methods of measuring perceptual disparities, with the help of EEG, oculography, etc. Key words: audiovisual translation, audiovisual materials, psycholinguistic experiment, scaling, German language